Pengaruh Zakat, Infak, dan Sedekah (ZIS) dan Pembiayaan Perbankan Syariah Terhadap Perekonomian di Indonesia Tahun 2012 - 2022 - Mochammad Cholil; Moehammad Fathorrazi; Lilis Yuliati (UPT Penerbitan Universitas Jember, 2024)
This research aims to examine and analyze the influence of Zakat, Infaq and Alms (ZIS) and sharia banking financing on the economy in Indonesia, both in the short and long term. The data in this research is secondary time series data in the form of quarters from 2012 to 2022. The analysis in this research uses VAR/VECM estimation with independent variables namely Zakat, Infaq and Alms (ZIS) and sharia banking financing while the dependent variable is Gross Domestic Product (GDP) Indonesia. The VECM estimation results in this research show that in the short term Zakat, Infaq and Alms (ZIS) during the past 3 quarters had a positive and significant effect on Indonesia's Gross Domestic Product (GDP), then in the long term Zakat, Infaq and Alms (ZIS) during 1 quarter ago had a positive and significant impact on Indonesia's Gross Domestic Product (GDP). Meanwhile, sharia banking financing (IBF) in the short term did not have a significant effect on Indonesia's Gross Domestic Product (GDP), while in the long term sharia banking financing (IBF) 1 quarter ago had a positive and significant effect on Indonesia's Gross Domestic Product (GDP).